The maze - DeMille, Nelson (New York : Scribner, 2022)
Called out of retirement by his former lover to investigate a serial killer targeting prostitutes, former NYPD Homicide Detective John Corey, as he digs deeper into these killings, which have garnered national attention, discovers that there are sinister forces at work that don$1 (Bt want this case solved.s
Keywords: Corey, John (Fictitious character) -- Fiction; Serial murder investigation -- Fiction; Prostitution -- Fiction; Man-woman relationships -- Fiction; New York (State) -- Fiction; Fire Island (N.Y.) -- Fiction; Detective and mystery fiction; Thrillers (Fiction)